An Electrocorticography Grid with Conductive Nanoparticles in a Polymer Thick Film on an Organic Substrate Improves CT and MR Imaging - Ahmadi, Emad (Radiology, 2016)
PURPOSE: To develop an electrocorticography (ECoG) grid by using deposition of conductive nanoparticles in a polymer thick film on an organic substrate (PTFOS) that induces minimal, if any, artifacts on computed tomographic (CT) and magnetic resonance (MR) images and is safe in terms of tissue reactivity and MR heating. MATERIALS AND METHODS: All procedures were approved by the Animal Care and Use Committee and complied with the Public Health Services Guide for the Care and Use of Animals. Electrical functioning of PTFOS for cortical recording and stimulation was tested in two mice. PTFOS disks were implanted in two mice; after 30 days, the tissues surrounding the implants were harvested, and tissue injury was studied by using immunostaining. Five neurosurgeons rated mechanical properties of PTFOS compared with conventional grids by using a three-level Likert scale. Temperature increases during 30 minutes of 3-T MR imaging were measured in a head phantom with no grid, a conventional grid, and a PTFOS grid. Two neuroradiologists rated artifacts on CT and MR images of a cadaveric head specimen with no grid, a conventional grid, and a PTFOS grid by using a four-level Likert scale, and the mean ratings were compared between grids. RESULTS: Oscillatory local field potentials were captured with cortical recordings. Cortical stimulations in motor cortex elicited muscle contractions. PTFOS implants caused no adverse tissue reaction. Mechanical properties were rated superior to conventional grids (χ(2) test, P < .05). The temperature increase during MR imaging for the three cases of no grid, PTFOS grid, and conventional grid was 3.84°C, 4.05°C, and 10.13°C, respectively. PTFOS induced no appreciable artifacts on CT and MR images, and PTFOS image quality was rated significantly higher than that with conventional grids (two-tailed t test, P < .05). CONCLUSION: PTFOS grids may be an attractive alternative to conventional ECoG grids with regard to mechanical properties, 3-T MR heating profile, and CT and MR imaging artifacts. (©) RSNA, 2016 Online supplemental material is available for this article.